2015
DOI: 10.1121/1.4916590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to intermittent and continuous 6–7 kHz sonar sweeps on harbor porpoise (Phocoena phocoena) hearing

Abstract: Safety criteria for mid-frequency naval sonar sounds are needed to protect harbor porpoise hearing. A porpoise was exposed to sequences of one-second 6-7 kHz sonar down-sweeps, with 10-200 sweeps in a sequence, at an average received sound pressure level (SPLav.re.) of 166 dB re 1 μPa, with duty cycles of 10% (intermittent sounds) and 100% (continuous). Behavioral hearing thresholds at 9.2 kHz were determined before and after exposure to the fatiguing noise, to quantify temporary hearing threshold shifts (TTS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 31 publications
(89 reference statements)
1
7
0
Order By: Relevance
“…Different TTS onset SEL thresholds have been measured in harbour porpoises for a variety of pulse types (Lucke et al, 2009;Kastelein et al, 2012bKastelein et al, , 2014bKastelein et al, , 2015aKastelein et al, , 2015b. Lucke et al (2009) determined a masked TTS-onset SEL level for a harbour porpoise subjected to single airgun transients, measuring auditory evoked potentials.…”
Section: Risk Thresholds For Hearing Loss For Harbour Porpoises Exposmentioning
confidence: 99%
See 2 more Smart Citations
“…Different TTS onset SEL thresholds have been measured in harbour porpoises for a variety of pulse types (Lucke et al, 2009;Kastelein et al, 2012bKastelein et al, , 2014bKastelein et al, , 2015aKastelein et al, , 2015b. Lucke et al (2009) determined a masked TTS-onset SEL level for a harbour porpoise subjected to single airgun transients, measuring auditory evoked potentials.…”
Section: Risk Thresholds For Hearing Loss For Harbour Porpoises Exposmentioning
confidence: 99%
“…Lucke et al (2009) determined a masked TTS-onset SEL level for a harbour porpoise subjected to single airgun transients, measuring auditory evoked potentials. As the sound stimuli of Lucke et al resembled explosion sound better than other TTS studies currently available (Kastelein et al, 2012b(Kastelein et al, , 2014b(Kastelein et al, , 2015a(Kastelein et al, , 2015bTougaard et al, 2015), our estimates for SEL thresholds for TTS and PTS were based on that study.…”
Section: Risk Thresholds For Hearing Loss For Harbour Porpoises Exposmentioning
confidence: 99%
See 1 more Smart Citation
“…The hearing of porpoise 06 for sounds in the range of the hearing test signals used in the present study (0.5-8 kHz) was tested (Kastelein et al, 2017), and was found to be representative for animals of his age and species; his hearing thresholds were within a few dB of those obtained from other young male porpoises tested with behavioral methods (Kastelein et al, 2002;Kastelein et al, 2009;Kastelein et al, 2010;Kastelein et al, 2015b).…”
Section: A Study Animal and Study Areamentioning
confidence: 80%
“…Besides the level of the sounds and the duration of the sequence, the duty cycle (signal duration, but especially the shot interval) can affect the induced TTS. Research has shown that the duty cycle of impulsive sounds affects the magnitude of TTS (Finneran et al, 2010;Kastelein et al, 2014a;Kastelein et al, 2015b), as hearing may recover, at least partly, between shots. Kastelein et al (2014a) reported that although exposure to a single sound did not lead to measurable TTS, the cumulative effect of sequences of sounds caused TTS.…”
Section: Introductionmentioning
confidence: 99%